Analisis Kualitas BOD, COD, Dan TSS Dalam Pengelolaan Limbah Cair Setelah Proses Koagulasi Dan Flokulasi Pada Instalasi Pengolahan Air Limbah (Studi Pada Industri Kosmetik X Di Kota Depok) Tahun 2022 - Sofianti Sofianti,; Ardiansyah Ardiansyah,; Susaldi Susaldi, (Student Scientific Creativity Journal, 2023)
The existence of the cosmetics industry basically has a positive impact but also creates new problems because there is still inadequate management of liquid waste. The aim of the study was to find out how the coagulation and flocculation processes affect the quality of BOD, COD, and TSS in wastewater treatment plants. This research method uses a qualitative type method, based on its type with a cross sectional approach with an observational researchhmethode. The populationnof this study is the outlet of the Wastewater Treatment Plant which has undergone coagulation and flocculation processes. The samples used were outlets after the coagulation and flocculation processes were carried out at the WWTP in Cosmetic Industry X, Depok City. The results from the inlet levels of BOD 2,152 mg/l, COD 5,380 mg/l, and TSS 1,830 mg/l. The outlet levels of the Cosmetic Industry X Wastewater Treatment Installation in Depok City showed a BOD level of 15 mg/l, a COD level of 63 mg/l, and a TSS of 20 mg/l. In this study the contents of BOD, COD and TSS in cosmetic industry waste X in Depok city were included in the water quality status with good quality after coagulation and flocculation processes.